2021
DOI: 10.1186/s13046-021-01978-8
|View full text |Cite
|
Sign up to set email alerts
|

Splicing factor SRSF1 promotes breast cancer progression via oncogenic splice switching of PTPMT1

Abstract: Background Intensive evidence has highlighted the effect of aberrant alternative splicing (AS) events on cancer progression when triggered by dysregulation of the SR protein family. Nonetheless, the underlying mechanism in breast cancer (BRCA) remains elusive. Here we sought to explore the molecular function of SRSF1 and identify the key AS events regulated by SRSF1 in BRCA. Methods We conducted a comprehensive analysis of the expression and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 66 publications
3
33
0
Order By: Relevance
“…SRSF1 is a splicing factor that also plays a proto-oncogene role by stimulating angiogenesis, cell growth, and cell proliferation [21][22][23]. Its oncogenic role has been characterized in numerous human cancers [12][13][14][15][16][17][18][21][22][23]. It has been found to be downregulated in unaffected brain parenchyma, as compared to human glioblastoma tissue, where it appears to influence tumor angiogenesis by stimulating the formation of the proangiogenic form of the vascular endothelial growth factor A (VEGFA) [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRSF1 is a splicing factor that also plays a proto-oncogene role by stimulating angiogenesis, cell growth, and cell proliferation [21][22][23]. Its oncogenic role has been characterized in numerous human cancers [12][13][14][15][16][17][18][21][22][23]. It has been found to be downregulated in unaffected brain parenchyma, as compared to human glioblastoma tissue, where it appears to influence tumor angiogenesis by stimulating the formation of the proangiogenic form of the vascular endothelial growth factor A (VEGFA) [14].…”
Section: Discussionmentioning
confidence: 99%
“…SRSF1 also exhibits several oncogenic functions, including the stimulation of angiogenesis, cell growth, and cell proliferation [12][13][14]. It has been found to be upregulated in numerous human malignancies, such as glioblastoma and breast carcinoma, as well as lung and colorectal cancer [12][13][14][15][16]. Recently, our research group also reported the poor prognostic role of SRSF1 in adult diffuse gliomas, prostate cancer, and mesotheliomas [17,18].…”
Section: Introductionmentioning
confidence: 87%
“…regulating the mitotic landscape [27]. SRSF1 also plays a direct role in promoting oncogenic pathways, in fact, in 2021 a study revealed that in breast cancer it is involved in alternative splicing promoting the overexpression of PTPMT1, which is related to breast cancer tumorigenesis through the P-AKT/C-MYC pathway [28].…”
Section: Breast Cancermentioning
confidence: 99%
“…Ubiquitination is an important regulatory mechanism of protein stability mediated by the ubiquitin-proteasome system ( Hershko, 1983 ). Several splicing factors have been found to be ubiquitinated and then degraded by proteasome ( Du et al, 2021 ). LncRNA can directly regulate SRSF6 protein stability or function.…”
Section: Regulatory Mechanisms Of Serine/arginine-rich Splicing Factor 6 Expression and Functionmentioning
confidence: 99%